A petition written in 1635 by the Kazan Tatars re-examined - Mаria Ivanics (Turkic Studies Journal, 2021)
The article examines the petition of religious Kazan Tatars to a high official of the Crimean khanate. The monument was first published in 1848 and translated into German, and the document is currently stored in Dresden. The authors of the petition Express their gratitude to the Crimean Khan for his conquests of Astrakhan and Kazan, for protection from the infidel Muslim peoples of the Volga Region. The document justifies the economic benefits of the conquered cities, from taxes collected from the population of the Volga region in the form of honey and furs. The author of the article reveals the historical background of the document creation, determines the date, addressees, and gives linguistic characteristics to the monument. The author notes that the document is not the original, that it is a translation of a text created later than the original. However, the petition recreates the idea of the original in historical, cultural, and linguistic terms. The author of the article emphasizes that at least one letter with such or similar content should have been written. The author also suggests that the addressee of the petition is undoubtedly the Crimean mufti or Crimean Khan, but not the Osman’s Sultan.